Synthesis of lead-free piezoelectric powders by ultrasonic-assisted hydrothermal method and properties of sintered (K0.48Na0.52)NBO3 ceramics - Isobe, G.; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics, Ferroelectrics, and Frequency Control, IEEE Transactions on)
(K,Na)NbO3 ceramics have attracted much attention as lead-free piezoelectric materials with high piezoelectric properties. High-quality (K,Na)NbO3 ceramics can be sintered using KNbO3 and NaNbO3 powders synthesized by a hydrothermal method. In this study, to enhance the quality factor of the ceramics, high-power ultrasonic irradiation was employed during the hydrothermal method, which led to a reduction in the particle size of the resultant powders.
Keywords: Q-factor; ceramics; crystal growth from solution; particle size; piezoelectric materials; potassium compounds; powders; sintering; sodium compounds; ultrasonic effects; (K0.48Na0.52)NbO3; KNbO3 powders; NaNbO3 powders; high-power ultrasonic irradiation; lead-free piezoelectric materials; lead-free piezoelectric powders; particle size reduction; piezoelectric properties; quality factor; sintered (K0.48Na0.52)NbO3 ceramics; sintering; ultrasonic-assisted hydrothermal method; Acoustics; Ceramics; Lead; Piezoelectric materials; Powders; Radiation effects; Transducers

Linear and nonlinear optical response of LiNbO3 calculated from first principles - Riefer, Arthur; Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics, and Frequency Control)

Ferroelectric phase transition in LiNbO3: Insights from molecular dynamics - Sanna, S.; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, W. G. (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)
The existence of localized vibrational modes both at the positive and at the negative LiNbO3 (0001) surface is demonstrated by means of first-principles calculations and Raman spectroscopy measurements. First, the phonon modes of the crystal bulk and of the (0001) surface are calculated within the density functional theory. In a second step, the Raman spectra of LiNbO3 bulk and of the two surfaces are measured. The phonon modes localized at the two surfaces are found to be substantially different, and are also found to differ from the bulk modes. The calculated and measured frequencies are in agreement within the error of the method. Raman spectroscopy is shown to be sensitive to differences between bulk and surface and between positive and negative surface. It represents therefore an alternative method to determine the surface polarity, which does not exploit the pyroelectric or piezoelectric properties of the material.

Vibrational properties of the LiNbO3 z-surfaces - Sanna, S.; Berth, Gerhard; Hahn, W.; Widhalm, A.; Zrenner, Artur; Schmidt, Wolf Gero (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)

Ultrasonic density sensor for liquids - Puttmer, A.; Hauptmann, P.; Henning, Bernd (IEEE Transactions on Ultrasonics, Ferroelectrics and Frequency Control)